Validation of Sysmex XT-2000iV generated quantitative bone marrow differential counts in untreated Wistar rats - Criswell, Kay A (Veterinary clinical pathology, 2014)
© 2014 American Society for Veterinary Clinical Pathology and European Society for Veterinary Clinical Pathology.